Nanoscale mechanical energy harvesting using piezoelectricity and flexoelectricity. (21st February 2017) - Liang, Xu; Hu, Shuling; Shen, Shengping
Abstract: Due to the electromechanical coupling effect, mechanical energy can be converted into electrical energy in certain materials. A theoretical framework is established to investigate the circuit voltage, electric power of nanoscale mechanical energy harvesting, in which the mechanical vibration energy was converted into electrical energy by piezoelectric and flexoelectric effects. Analytical solutions for the maximum electric potential, circuit voltage and electric power generated in bent BaTiO3 (BT), ZnO nanowires (NWs) and Pb(Mg1/3 Nb2/3 )O3 (PMN) nanofilms (NFs) were derived. Static and dynamic analyses are conducted to obtain the fundamental information of these mechanical energy harvestings. Different from the previous studies, the flexoelectric-mechanism are included in the fundamental mechanical frameworks. The maximum electric potential generated in the BT, ZnO NWs and PMN NF is found to be enhanced by flexoelectricity in the static case, meanwhile the circuit voltage and electric power are dramatic enhanced by flexoelectricity when the geometric dimensions shrinks to dozens of nanometers. The mechanical limitation condition is employed to calculate the practical maximum electric potential, circuit voltage and electric power. This work tries to provide a comprehensive understanding of the mechanical energy harvesting capability of these nanoscale structures and provide valuable information for designing flexoelectricity-based nanogenerator devices.